Complete mitochondrial genome of a tropical sea cucumber, Stichopus chloronotus - Xiaoying Chen; Yuping Sun; Hongxia Zhao; Junru Hu; Bing Chen; Huo Li; Wen Huang (Mitochondrial DNA. Part B. Resources, 2021)
In this study, we report the complete mitochondrial genome of Stichopus chloronotus. The mitogenome was 16,247 base pairs (58.55% A + T content) in length, comprising a total of 37 genes, including 13 protein-coding genes, 22 transfer RNA genes and 2 ribosomal RNA genes. To resolve the phylogenetic position of S. chloronotus, we analyzed all mitochondrial protein-coding genes from 27 species within the Echinodermata. The results showed that S. chloronotus belonged to the family Stichopodidae and was more closely related to tropical Stichopus species (S. horrens and S. monotuberculatus) than to other species. Our results will be useful for evolutionary analysis of sea cucumber species.